Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Rearrange 8x-y=-13 to y=8x+13
Substitute this in so:
6x-3(8x+13)=15
6x-24x-39=15
-18x-39=15
-18x=54
x=-3
Substitute x into 1st equation:
Y=(8*-3)+13
Y=-24+13
Y=-11
Substitute this in so:
6x-3(8x+13)=15
6x-24x-39=15
-18x-39=15
-18x=54
x=-3
Substitute x into 1st equation:
Y=(8*-3)+13
Y=-24+13
Y=-11
[tex]\begin{cases} 8x-y=-13 \\ 6x-3y=15 \end{cases}\\ \\ \begin{cases} -y=-8x-13 \ \ *(-1) \\ 6x-3y=15 \end{cases}\\ \\\begin{cases} y= 8x+13 \\ 6x-3(8x+13)=15 \end{cases} \\ \\\begin{cases} y= 8x+13 \\ 6x-24x-39=15 \end{cases}[/tex]
[tex]\begin{cases} y= 8x+13 \\ 6x-24x =15+39 \end{cases} \\ \\\begin{cases} y= 8x+13 \\ -18x =54 \ \ / :(-18)\end{cases} \\ \\\begin{cases} y= 8*(-3)+13 \\ x = -3 \end{cases} \\ \\\begin{cases} y= -24+13 \\ x = -3 \end{cases} \\ \\ \begin{cases} y= -11 \\ x = -3 \end{cases}[/tex]
[tex]\begin{cases} y= 8x+13 \\ 6x-24x =15+39 \end{cases} \\ \\\begin{cases} y= 8x+13 \\ -18x =54 \ \ / :(-18)\end{cases} \\ \\\begin{cases} y= 8*(-3)+13 \\ x = -3 \end{cases} \\ \\\begin{cases} y= -24+13 \\ x = -3 \end{cases} \\ \\ \begin{cases} y= -11 \\ x = -3 \end{cases}[/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.